Pengaruh Budaya Organisasi, Kepemimpinan, Dan Komitmen Terhadap Retensi Karyawan Pada PT. Harindo Jaya Nusantara Jakarta - Wistan Laia, Petrus; Septiani, Yeni (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. The purpose of this study is to determine the influence of Organizational Culture, Leadership, and Commitment on Employee Retention at PT Harindo Jaya Nusantara, both partially and simultaneously. The method used is quantitative. The sampling technique used is non-probability sampling with the Slovin technique, and a sample of 110 respondents was obtained. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests with the help of SPSS 25 software. The results of this study indicate that organizational culture has a significant effect on employee retention with a determination coefficient value of 7.9% and hypothesis testing obtained t-count > t-table or (3.222 > 1.659). Leadership has a significant effect on employee retention with a determination coefficient value of 29.5% and hypothesis testing obtained t-count > t-table or (6.821 > 1.659). Commitment has a significant effect on employee retention with a determination coefficient value of 4.3% and hypothesis testing obtained t-count > t-table or (2.438 > 1.659). Organizational culture, leadership, and commitment simultaneously have a significant effect on employee retention with the regression equation Y = 28.349 + (-0.491X1) + 0.909X2 + (-0.133X3). The determination coefficient value is 35.9%, while the remaining 64.1% is influenced by other factors. Hypothesis testing obtained F-count > F-table or (21.257 > 2.69). Keywords: Organizational Culture, Leadership, Commitment, Employee Retention